Variable Temperature 57Fe-Mössbauer Spectroscopy Study of Nanoparticle Iron Carbides - Alex Scrimshire; Alex L. Lobera; Roman Kultyshev; Peter Ellis; Susan D. Forder; Paul A. Bingham (Croatica Chemica Acta, 2015)
Near-phase-pure nanoparticle iron carbides (Fe3C and Fe5C2) were synthesised. Debye model calculations were used with hyperfine parameters gathered by 57Fe Mössbauer spectroscopy within a temperature range of 10 K to 293 K, with analysis providing Debye temperatures of 422 K and 364 K for two Fe sites in Fe5C2 and 355 K for ferromagnetic Fe3C. The intrinsic isomer shifts were calculated as 0.45 mm s−1 and 0.43 mm s−1 for iron sites 1 and 2 respectively in Fe5C2 and 0.42 mm s−1 for Fe3C. Recoil-free fractions for the two iron sites were also calculated at f300 0.785 and 0.726 for site 1 and 2 respectively.